Oscillatory Light‐Emitting Biopolymer Based Janus Microswimmers. Issue 10 (11th March 2020) - María‐Hormigos, Roberto; Escarpa, Alberto; Goudeau, Bertrand; Ravaine, Valérie; Perro, Adeline; Kuhn, Alexander
Abstract: Janus particles with a double functionality are synthesized by asymmetric loading of alginate hydrogel beads with Prussian Blue, leading to microswimmers with an original dynamic oscillatory behavior coupled to chemical light emission. This phenomenon results from the combination of two features: 1) Prussian Blue in the gel acts as a catalyst and enables concomitant light emission and oxygen production in the presence of luminol and hydrogen peroxide; 2) the hydrogel particle has a differential porosity distribution, leading to an asymmetric release of oxygen bubbles propelling the particle. The synthesis of these functional materials is achieved using an electric field based symmetry breaking approach with ionically cross‐linked alginate beads and can be applied to a wide range of particle sizes. Such light‐emitting swimmers open up interesting perspectives for the elaboration of autonomous dynamic chemical systems. Abstract : Non‐conductive Janus alginate particles are synthesized via an electrochemical process. Water electrolysis triggers pH gradients allowing the generation of an asymmetric porosity. These particles are loaded with Prussian Blue precipitates. Prussian Blue catalyzes the formation of oxygen bubbles, which create a buoyancy shift, and enables the chemiluminescence of luminol, turning the particles into light‐emitting swimmers.